Preservative Equipment Based on Nitrogen Doping Titanium Dioxide Photocatalyst White Oyster Mushroom In Banyumeneng - Sri Winarni; Windi Permatasari; D. Dayanti; E. G. Savio; I. Khairunnisa (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
Oyster mushrooms easily wilt and turn brown because of bacteria and enzymatic reactions. Preservation of oyster mushrooms has been done in the freezer, which can only last 3-4 days. In addition, preservation using chemicals can cause side effects such as diarrhea to long-term cancer. The purpose of this study was to determine the shelf life of white oyster mushroom products using the innovation of making preservatives with titanium dioxide doped nitrogen (N-TiO2). The method used is the sol-gel method with TiCl4 as the precursor of TiO2 and diethylamine as the nitrogen-doped precursor. N-Doped TiO2 was characterized using FTIR, XRD, and antibacterial activity tests. The results of the FTIR spectrometer showed peaks at 518 and 678 cm-1, which indicated the presence of vibrations from TiO2. Analysis of the crystalline phase of TiO2 using XRD obtained a mixed phase in the form of anatase with peaks at 55.10 (2Ø) and rutile at 27.40 (2Ø). Anti-bacterial activity test showed that N-TiO2 was able to inhibit the growth of E. coli bacteria by 6.48±0.42 mm. The results of the organoleptic test showed that preservation using photocatalyst can extend the preservation time of oyster mushrooms, which is about 6-9 days, longer than the ideal preservation time of oyster mushrooms. This technological innovation can answer the problems of oyster mushroom farmers in Banyumeneng Village related to oyster mushroom harvests that are wasted because they are rotten and cannot be sold.